Synthesis of aryl sulfides via radical–radical cross coupling of electron-rich arenes using visible light photoredox catalysis - Das, Amrita; Maity, Mitasree; Malcherek, Simon; König, Burkhard; Rehbein, Julia (Beilstein Journal of Organic Chemistry, 2018)
Electron-rich arenes react with aryl and alkyl disulfides in the presence of catalytic amounts of [Ir(dF(CF3)ppy)2(dtbpy)]PF6 and (NH4)2S2O8 under blue light irradiation to yield arylthiols. The reaction proceeds at room temperature and avoids the use of prefunctionalized arenes. Experimental evidence suggests a radical–radical cross coupling mechanism.
Keywords: arenes; oxidation; photocatalysis; thiolation; visible light

(untitled) - Dunbar, K. L.; Scharf, D. H.; Litomska, A.; Hertweck, C. (Chem. Rev., 2017)

(untitled) - Vazquez-Prieto, M. A.; Miatello, R. M. (Mol. Aspects Med., 2010)

(untitled) - Feng, M.; Tang, B.; Liang, S. H.; Jiang, X. (Curr. Top. Med. Chem., 2016)

(untitled) - Kondo, T.; Mitsudo, T.-a. (Chem. Rev., 2000)

(untitled) - Eichman, C. C.; Stambuli, J. P. (Molecules, 2011)

(untitled) - Wong, Y.-C.; Jayanth, T. T.; Cheng, C.-H. (Org. Lett., 2006)

(untitled) - Singh, R.; Allam, B. K.; Singh, N.; Kumari, K.; Singh, S. K.; Singh, K. N. (Adv. Synth. Catal., 2015)

(untitled) - Pandya, V. G.; Mhaske, S. B. (Org. Lett., 2014)

(untitled) - Li, Y.; Xie, W.; Jiang, X. (Chem. – Eur. J., 2015)

(untitled) - Li, G. Y. (Angew. Chem., Int. Ed., 2001)

(untitled) - Fernández-Rodríguez, M. A.; Hartwig, J. F. (Chem. – Eur. J., 2010)

(untitled) - Teverovskiy, G.; Surry, D. S.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2011)

(untitled) - Li, J.; Li, C.; Yang, S.; An, Y.; Wu, W.; Jiang, H. (J. Org. Chem., 2016)

(untitled) - Gan, J.; Ma, D. (Org. Lett., 2009)

(untitled) - Saha, A.; Saha, D.; Ranu, B. C. (Org. Biomol. Chem., 2009)

(untitled) - Ma, D.; Xie, S.; Xue, P.; Zhang, X.; Dong, J.; Jiang, Y. (Angew. Chem., Int. Ed., 2009)

(untitled) - Ma, D.; Geng, Q.; Zhang, H.; Jiang, Y. (Angew. Chem., Int. Ed., 2010)

(untitled) - Chen, C.-K.; Chen, Y.-W.; Lin, C.-H.; Lin, H.-P.; Lee, C.-F. (Chem. Commun., 2010)

(untitled) - Ma, D.; Lu, X.; Shi, L.; Zhang, H.; Jiang, Y.; Liu, X. (Angew. Chem., Int. Ed., 2011)

(untitled) - Deng, H.; Li, Z.; Ke, F.; Zhou, X. (Chem. – Eur. J., 2012)

(untitled) - Uyeda, C.; Tan, Y.; Fu, G. C.; Peters, J. C. (J. Am. Chem. Soc., 2013)

(untitled) - Zhang, Y.; Ngeow, K. C.; Ying, J. Y. (Org. Lett., 2007)

(untitled) - Jammi, S.; Barua, P.; Rout, L.; Saha, P.; Punniyamurthy, T. (Tetrahedron Lett., 2008)

(untitled) - Zhang, C. P.; Vicic, D. A. (J. Am. Chem. Soc., 2012)

(untitled) - Correa, A.; Mancheño, O. G.; Bolm, C. (Chem. Soc. Rev., 2008)

(untitled) - Correa, A.; Carril, M.; Bolm, C. (Angew. Chem., Int. Ed., 2008)

(untitled) - Wu, W.-Y.; Wang, J.-C.; Tsai, F.-Y. (Green Chem., 2009)

(untitled) - Wu, J.-R.; Lin, C.-H.; Lee, C.-F. (Chem. Commun., 2009)

(untitled) - Lin, Y.-Y.; Wang, Y.-J.; Lin, C.-H.; Cheng, J.-H.; Lee, C.-F. (J. Org. Chem., 2012)

(untitled) - Wong, Y.-C.; Jayanth, T. T.; Cheng, C.-H. (Org. Lett., 2006)

(untitled) - Lan, M.-T.; Wu, W.-Y.; Huang, S.-H.; Luo, K.-L.; Tsai, F.-Y. (RSC Adv., 2011)

(untitled) - Huang, X.; Chen, Y.; Zhen, S.; Song, L.; Gao, M.; Zhang, P.; Li, H.; Yuan, B.; Yang, G. (J. Org. Chem., 2018)

(untitled) - Ajiki, K.; Hirano, M.; Tanaka, K. (Org. Lett., 2005)

(untitled) - Arisawa, M.; Suzuki, T.; Ishikawa, T.; Yamaguchi, M. (J. Am. Chem. Soc., 2008)

(untitled) - Cheng, J.-H.; Ramesh, C.; Kao, H.-L.; Wang, Y.-J.; Chan, C.-C.; Lee, C.-F. (J. Org. Chem., 2012)

(untitled) - Yonova, I. M.; Osborne, C. A.; Morrissette, N. S.; Jarvo, E. R. (J. Org. Chem., 2014)

(untitled) - Shen, C.; Zhang, P.; Sun, Q.; Bai, S.; Hor, T. S. A.; Liu, X. (Chem. Soc. Rev., 2015)

(untitled) - Parumala, S. K. R.; Peddinti, R. K. (Green Chem., 2015)

(untitled) - Zhao, W.; Xie, P.; Bian, Z.; Zhou, A.; Ge, H.; Niu, B.; Ding, Y. (RSC Adv., 2015)

(untitled) - Huang, Z.; Zhang, D.; Qi, X.; Yan, Z.; Wang, M.; Yan, H.; Lei, A. (Org. Lett., 2016)

(untitled) - Liu, B.; Lim, C.-H.; Miyake, G. M. (J. Am. Chem. Soc., 2017)

(untitled) - Guo, W.; Tan, W.; Zhao, M.; Tao, K.; Zheng, L.-Y.; Wu, Y.; Chen, D.; Fan, X.-L. (RSC Adv., 2017)

(untitled) - Rahaman, R.; Das, S.; Barman, P. (Green Chem., 2018)

(untitled) - Giordan, J.; Bock, H. (Chem. Ber., 1982)

(untitled) - Töteberg-Kaulen, S.; Steckhan, E. (Tetrahedron, 1988)

(untitled) - Lakkaraju, P. S.; Zhou, D.; Roth, H. D. (J. Chem. Soc., Perkin Trans. 2, 1998)

(untitled) - Wallace, W. L.; Van Duyne, R. P.; Lewis, F. D. (J. Am. Chem. Soc., 1976)

(untitled) - Dénès, F.; Pichowicz, M.; Povie, G.; Renaud, P. (Chem. Rev., 2014)

(untitled) - Romero, N. A.; Nicewicz, D. A. (J. Am. Chem. Soc., 2014)

(untitled) - Dogadkin, D. N.; Dolotova, E. V.; Soboleva, I. V.; Kuzmin, M. G.; Plyusnin, V. F.; Pozdnyakov, I. P.; Grivin, V. P.; Vauthey, E.; Brodard, P.; Nicolet, O. (High Energy Chem., 2004)

(untitled) - Lu, Y.; Wang, J.; McGoldrick, N.; Cui, X.; Zhao, J.; Caverly, C.; Twamley, B.; Ó Máille, G. M.; Irwin, B.; Conway-Kenny, R.; Draper, S. M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Flamigni, L.; Ventura, B.; Barigelletti, F.; Baranoff, E.; Collin, J.-P.; Sauvage, J.-P. (Eur. J. Inorg. Chem., 2005)

(untitled) - Hofbeck, T.; Yersin, H. (Inorg. Chem., 2010)